2011
DOI: 10.1002/jsfa.4294
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of volatile compounds in Chinese soy sauce aroma type liquor by stir bar sorptive extraction and gas chromatography–mass spectrometry

Abstract: SBSE is a fast, simple, effective, and reliable method for extracting volatile compounds from Chinese liquor. The chemometrics approach revealed that LJ liquor with soy sauce aroma could exhibit more prominent sauce flavor through extending the time of storage, and its peculiar manufacturing practice was responsible for the soy sauce flavor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 16 publications
5
73
0
Order By: Relevance
“…Generally, esters are found in fermented food, which are derived from esterification of alcohols with carboxylic acids formed by microbial and enzymatic decomposition of lipids. In this study, a total of 8 esters were detected and most of the esters detected in this study had been previously found in soybean paste, miso or soy sauce (Fan et al, 2011;Sun et al, 2010;Zhao et al, 2011). A detailed comparison showed that higher contents of ethyl esters were detected compared with methyl esters, which was in agreement with previous research in soybean paste (Zhao et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…Generally, esters are found in fermented food, which are derived from esterification of alcohols with carboxylic acids formed by microbial and enzymatic decomposition of lipids. In this study, a total of 8 esters were detected and most of the esters detected in this study had been previously found in soybean paste, miso or soy sauce (Fan et al, 2011;Sun et al, 2010;Zhao et al, 2011). A detailed comparison showed that higher contents of ethyl esters were detected compared with methyl esters, which was in agreement with previous research in soybean paste (Zhao et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…Shukui Zhu et al developed a method to characterize the volatile compounds in Moutai liquor (sauce‐aroma liquor) by comprehensive two‐dimensional gas chromatography/time of‐flight mass spectrometry and 528 components were identified. Wenlai Fan et al characterized the volatile compounds in Chinese soy sauce aroma type liquor by stir bar sorptive extraction and gas chromatography–mass spectrometry (SBSE/GC‐MS). However, no comparison of the volatiles and aroma sensory profiles of the three aroma type Chinese liquors has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster analysis (CA), discriminant analysis (DA), principal component analysis (PCA) and partial least square (PLS) regression have been widely adopted statistical methods in recent years. All these approaches have shown good performance in many cases of liquor fl avour research, such as spectral analysis (8), artifi cial nose (9), liquor discrimination and identifi cation (10)(11)(12). However, most of these methods are linear in nature, thus may not be capable of describing non-linear systems satisfactorily.…”
Section: Introductionmentioning
confidence: 99%